Pablo Antonio Cuadra, tierra y luz nicaragüense - Martín-Baró, Ignacio (ECA: Estudios Centroamericanos, 1966)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 21, No. 215, 1966: 93-95.